Geomorphic Evidence for the Presence of Ice Deposits in the Permanently Shadowed Regions of Scott‐E Crater on the Moon. Issue 2 (18th January 2021) - Moon, Seulgi; Paige, David A; Siegler, Matthew A; Russell, Patrick S
Abstract: The abundance and distribution of ice on the Moon are still unknown. Here, we examine the connections between geomorphic characteristics and the potential presence of lunar ice in permanently shadowed regions of the Scott‐E crater in the lunar south polar region. We first quantify surface characteristics, such as roughness, based on high‐resolution optical images and topography data and then model spatial variations of water ice stability using a high‐resolution thermal model. We find that the surface roughness in regions where thermally stable surface ice is predicted is significantly lower than in adjacent regions where subsurface ice or no ice is predicted. This correspondence may result from processes such as preferential cold‐trapping in depressions or high albedo areas, or enhanced regolith transport in the ice‐rich regolith. Plain Language Summary: Permanently shadowed regions (PSRs) near the lunar north and south poles are never exposed to direct sunlight. As a result, these regions have extremely low temperatures and have a high potential for hosting water ice on the surface or in the shallow subsurface. However, few studies have shown unequivocal evidence for the presence of lunar ice deposits in PSRs. In this study, we examine whether surface or subsurface ice may cause measurable changes in surface characteristics of the Moon. To show this, we quantify the spatial variation of surface roughness and model ice stability on the surface and subsurface in a PSR in the lunar south polar region. We find that areas where thermal models predict stable surface ice tend to have subdued surface roughness variations. This may be caused by enhanced transport of ice‐rich surface material or preferential trapping of ice in local low‐elevation areas or high albedo areas. Key Points: We quantify lunar surface roughness using high‐resolution optical images and topography and model the stability of near‐surface water ice Surface roughness in regions where surface water ice is predicted to be thermally stable is lower than in warmer areas Cold‐trapping of ice or enhanced ice‐rich regolith transport may lead to the reduced small‐scale topographic roughness